2008
DOI: 10.1038/bmt.2008.386
|View full text |Cite
|
Sign up to set email alerts
|

Management of HSV, VZV and EBV infections in patients with hematological malignancies and after SCT: guidelines from the Second European Conference on Infections in Leukemia

Abstract: These guidelines on the management of HSV, VZV and EBV infection in patients with hematological malignancies and after SCT were prepared by the European Conference on Infections in Leukemia following a predefined methodology. A PubMed search was conducted using the appropriate key words to identify studies pertinent to management of HSV, VZV and EBV infections. References of relevant articles and abstracts from recent hematology and SCT scientific meetings were also reviewed. Prospective and retrospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
364
2
29

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(411 citation statements)
references
References 158 publications
9
364
2
29
Order By: Relevance
“…This case suggests that performing a biopsy in the initial stage of the disease is essential for confirming the diagnosis of PTLD (17) and that a sequential analysis to identify the lineage of the EBV-infected cells should be conducted when administering rituximab in patients with a high level of EBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…This case suggests that performing a biopsy in the initial stage of the disease is essential for confirming the diagnosis of PTLD (17) and that a sequential analysis to identify the lineage of the EBV-infected cells should be conducted when administering rituximab in patients with a high level of EBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…or 40 mg/kg/body weight every 8 hours for 7-21 days until complete healing of lesions. Cidofovir is recommended at a dose of 5 mg/kg/body weight, once a week for 2 weeks of treatment [11]. Acyclovir prophylaxis is indicated in seropositive patients.…”
Section: Discussionmentioning
confidence: 99%
“…It becomes ineffective in the case of mutation of the genome of HSV-1 virus consisting in deficiency of thymidine kinase [10]. Alternative drugs for resistance to acyclovir are: foscarnet, valganyclovir and cidofovir, which act independently of the level of thymidine kinase [1,11,12]. Foscarnet is used at a dose of 60 mg/kg/body weight every 12 hours i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,28 In addition, an ever growing number of studies suggested that preemptive therapy with rituximab may be highly effective in controlling viral proliferation and avoiding progression into EBV-related LPD. 29,30 Of note, the efficacy of rituximab was mainly observed in the preemptive setting, but to a lesser extent once EBV-related LPD was fully established.…”
Section: Discussionmentioning
confidence: 99%